2016
DOI: 10.1038/ncomms12868
|View full text |Cite
|
Sign up to set email alerts
|

Local microRNA delivery targets Palladin and prevents metastatic breast cancer

Abstract: Metastasis is the primary cause for mortality in breast cancer. MicroRNAs, gene expression master regulators, constitute an attractive candidate to control metastasis. Here we show that breast cancer metastasis can be prevented by miR-96 or miR-182 treatment, and decipher the mechanism of action. We found that miR-96/miR-182 downregulate Palladin protein levels, thereby reducing breast cancer cell migration and invasion. A common SNP, rs1071738, at the miR-96/miR-182-binding site within the Palladin 3′-UTR abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
134
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 156 publications
(153 citation statements)
references
References 56 publications
3
134
0
Order By: Relevance
“…Many of the same authors were also involved in another study involving local miR-96 or miR-182 treatment for targeting Palladin, a gene involved in the invasive behavior of breast cancer cells, thereby preventing metastatic breast cancer. [172] An oxidized AuNP-dextran-dendrimer based hydrogel system was used to provide an effective local, selective, and sustained release of miR-96/miR-182, and demonstrated prominent suppression of metastasis in a mouse breast cancer model. By combining the codelivery of miRNAs with the chemotherapy drug, cisplatin, significant primary tumor reduction and metastasis inhibition were obtained.…”
Section: Other Tissue Types: Cancer Treatmentsmentioning
confidence: 99%
“…Many of the same authors were also involved in another study involving local miR-96 or miR-182 treatment for targeting Palladin, a gene involved in the invasive behavior of breast cancer cells, thereby preventing metastatic breast cancer. [172] An oxidized AuNP-dextran-dendrimer based hydrogel system was used to provide an effective local, selective, and sustained release of miR-96/miR-182, and demonstrated prominent suppression of metastasis in a mouse breast cancer model. By combining the codelivery of miRNAs with the chemotherapy drug, cisplatin, significant primary tumor reduction and metastasis inhibition were obtained.…”
Section: Other Tissue Types: Cancer Treatmentsmentioning
confidence: 99%
“…This study introduces the therapeutic potential of miRNAs in breast cancer metastasis prevention. This novel combined therapy can definitely improve the clinical outcome by significantly reducing primary tumor mass, as well as reducing -or even preventingmetastasis [30].…”
Section: Facing the Truth: Local Over Sys-temicmentioning
confidence: 99%
“…However, Gilam et al reported the development of a local hydrogel platform applied in a primary breast tumor, which is able to prevent the establishment of metastasis in the lungs, liver and brain [30], just by targeting and modulating the primary tumor microenvironment. In this study the authors developed a smart delivery vehicle based on hydrogel-embedded gold-nanoparticles providing efficient local and selective sustained release of miR-96 and miR-182, as well as combined therapy of miRNAs with a chemotherapy drug, which dramatically suppressed metastasis in an in vivo orthotopic breast cancer mouse model.…”
Section: Facing the Truth: Local Over Sys-temicmentioning
confidence: 99%
“…RNA-based therapeutics, such as small-interfering (siRNAs), microRNAs (miRNAs), antisense oligonucleotides (ASOs), aptamers, synthetic mRNAs and CRISPR-Cas9, there is great potential to attack genes and genetic products that are currently untreatable, and to produce a new treatment model in the disease [82][83][84] . Since the first RNA interference report (RNAi) in 1998, there has been great interest in applying RNAi therapy to inhibit histopathological gene expression.…”
Section: Gene Deliverymentioning
confidence: 99%